2007
DOI: 10.1086/519930
|View full text |Cite
|
Sign up to set email alerts
|

Use of Decolonization to Prevent Staphylococcal Infections in Various Healthcare Settings: Results of an Emerging Infections Network Survey

Abstract: Less than 20% of infectious diseases consultants work in hospitals that routinely employ decolonization therapy for individuals with staphylococcal carriage undergoing elective surgical procedures or for infection control efforts to limit nosocomial transmission of methicillin-resistant Staphylococcus aureus (MRSA). However, infectious diseases consultants frequently encounter patients with recurrent MRSA furunculosis and attempt to decolonize them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…No mupirocin resistance was detected in the 199 MRSA isolates tested [30]. A more common use of nasal mupirocin in community settings is eradication of colonization to prevent recurrent infection in individual patients with furunculosis [49]. In one study, 34 patients with recurrent staphylococcal infection were treated with a 5-day course of mupirocin, and 17 were randomly selected to receive monthly 5-day mupirocin courses.…”
Section: Treatment and Prevention Of Community-associated Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…No mupirocin resistance was detected in the 199 MRSA isolates tested [30]. A more common use of nasal mupirocin in community settings is eradication of colonization to prevent recurrent infection in individual patients with furunculosis [49]. In one study, 34 patients with recurrent staphylococcal infection were treated with a 5-day course of mupirocin, and 17 were randomly selected to receive monthly 5-day mupirocin courses.…”
Section: Treatment and Prevention Of Community-associated Infectionmentioning
confidence: 99%
“…First, the incidence of community-associated skin and soft-tissue infection has apparently increased in the United States in recent years, likely driven by the emergence of community-associated MRSA strains [58]. In an effort to prevent the recurrence of skin and soft-tissue infection often associated with these strains, clinicians may increase use of mupirocin to eradicate MRSA colonization in patients and their families [49,[59][60][61][62].…”
Section: Will Mupirocin Resistance Become More Prevalent In the Unitementioning
confidence: 99%
See 1 more Smart Citation
“…This, along with the increased use of mupirocin for prevention of recurrent skin and soft tissue MRSA infections (47)(48)(49), and growing interest in perioperative eradication of MRSA for the prevention of SSIs has important implications for the spread of mupirocin resistance (50). In 2002, Deshpande et al (51) performed an extensive study of mupirocin resistance and noted a marked increase globally compared to an earlier study.…”
Section: Discussionmentioning
confidence: 99%
“…An Emerging Infections Network survey of the use of decolonization to prevent staphylococcal infections in various health care settings found that !20% of infectious diseases consultants work in hospitals that routinely use decolonization therapy for individuals with staphylococcal carriage, either for carrier patients undergoing elective surgery or for infection control of MRSA [122]. Nevertheless, these consultants often attempt to decolonize patients with MRSA furunculosis.…”
Section: Prevention Of Mrsamentioning
confidence: 99%